Azizah... with deep affection / Saidatul Akmar Ismail - Ismail, Prof. Madya Dr. Saidatul Akmar (Universiti Teknologi MARA Cawangan Kedah, 2022)
A compilation of poems from interested 118 lecturers and academicians from UiTM and other higher learning institutions.